2014
DOI: 10.4236/jilsa.2014.61002
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network Approach to Predicting Car Tyre Micro-Scale and Macro-Scale Behaviour

Abstract: Finite Element (FE) analysis has become the favoured tool in the tyre industry for virtual development of tyres because of the ability to represent the detailed lay-up of the tyre carcass. However, application of FE analysis in tyre design and development is still very time-consuming and expensive. Here, the application of various Artificial Neural Network (ANN) architectures to predicting tyre performance is assessed to select the most effective and efficient architecture, to allow extensive parametric studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The contact pressure pattern generated agrees with that of the literature [36][37][38]. During cornering, the dual-chambers demonstrated a marginal reduction in the lateral force which may undermine from the tire's grip and stability a little.…”
Section: Fe Model Validationsupporting
confidence: 86%
“…The contact pressure pattern generated agrees with that of the literature [36][37][38]. During cornering, the dual-chambers demonstrated a marginal reduction in the lateral force which may undermine from the tire's grip and stability a little.…”
Section: Fe Model Validationsupporting
confidence: 86%
“…It has been concluded that ANNs can be used as a very powerful and simple alternative technique for the prediction of an optimum cure time to equivalent cure concept, which is traditionally used in the rubber and tire industries. In the work [41], the effective and efficient ANN architecture was found to optimize tire design before an expensive finite element analysis used to confirm the predicted tire performance. Generally speaking, there are few publications about the use of ANNs in the area of polymeric materials or rubbers up to now.…”
Section: Introductionmentioning
confidence: 99%
“…For traffic information prediction, between numerous nonparametric prediction approaches most often are used artificial neural networks (ANN), support vector regression (SVR), and the adaptive neurofuzzy system (ANFIS)) [15][16][17][18]. The main advantage of the artificial neural network (ANN) is its ability to model very complex multivariable systems, and the quality of prediction is tuned and improved by parameters of the network such as the number of hidden neurons and learning factor [19]. The neural network prediction of the speed profile in transport systems is presented in [15][16].…”
Section: Introductionmentioning
confidence: 99%